A novel sub-seabed CO2 release experiment informing monitoring and impact assessment for geological carbon storage. (July 2015) - Taylor, Peter; Stahl, Henrik; Vardy, Mark E.; Bull, Jonathan M.; Akhurst, Maxine; Hauton, Chris; James, Rachel H.; Lichtschlag, Anna; Long, Dave; Aleynik, Dmitry; Toberman, Matthew; Naylor, Mark; et al.
Highlights: A unique and novel CO2 release experiment in the marine environment. Field-scale simulated leak of CO2 gas from a carbon capture and storage facility. Experimental design and set-up for the QICS experiment, conducted during the summer of 2012. Abstract: Carbon capture and storage is a mitigation strategy that can be used to aid the reduction of anthropogenic CO2 emissions. This process aims to capture CO2 from large point-source emitters and transport it to a long-term storage site. For much of Europe, these deep storage sites are anticipated to be sited below the sea bed on continental shelves. A key operational requirement is an understanding of best practice of monitoring for potential leakage and of the environmental impact that could result from a diffusive leak from a storage complex. Here we describe a controlled CO2 release experiment beneath the seabed, which overcomes the limitations of laboratory simulations and natural analogues. The complex processes involved in setting up the experimental facility and ensuring its successful operation are discussed, including site selection, permissions, communications and facility construction. The experimental design and observational strategy are reviewed with respect to scientific outcomes along with lessons learnt in order to facilitate any similar future.